Genesis of German poetry of love and holiness (The Song of Songs in Martin Opitz’s interpretation) - Sinilo, Galina V. (Journal of the Belarusian State University. Philology, 2019)
This research paper investigates the first holistic German paraphrase of The Song of Songs carried out by Martin Opitz (1597–1639), the founder of the modern-period German poetry. We show that The Song of Songs is one of the key archetexts serving both content- and text-generating functions as well as defining genre searching for Opitz. Seeing The Song of Songs as a lyric-dramatic pastoral poem or a lyrical pastoral drama, Opitz creates a similar genre in German lite- rature. In the free and close-to-biblical text paraphrase of The Song of Songs, which is the author’s commentary (metatext) on it, he puts into practice synthesis of love-erotic and religious poetry for the first time in German language, creates the poetry of love and holiness. For the poet, The Song of Songs is a distinctive utopia of beauty and harmony juxtaposed with the disgraceful reality of the tragic period of the Thirty Years’ War. Love praised by The Song of Songs is interpreted by the poet as a power that transfigures life and vanquishes death. We argue that the work on the paraphrase of The Song of Songs becomes a creative laboratory, where the poet’s distinctive style combining rationalism, thought severity of classicism, striking plasticity, picturesqueness and metaphors associated with baroque thinking is born. Opitz’s poetics manner, compared with unstable plasticity of The Song of Songs conveying dynamics of spirit, is more oriented towards «sculptural» images. In his interpretation of the biblical poem M. Opitz is the first poet in German literature who develops the motif of opposition of the hustle of urban civilization and harmony of rural life in accordance with natural divine law – the law of love. This motif, later developed by baroque poets, anticipates the searches of the Age of the Enlightenment, especially of the writers of sentimentalism.